U ui v j f a b u du

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Ò Ò º ÐÐ × Ñ ÐÐØ ÔÙÒ Ø (p1 , p2 , . . . , pn ) D(f ) lim Ä ØÙÑ f ÚÖ ÐÐ n Ö ÝØ ×Ø Ö ÙÑ × ÐÖ ÒØ ÑÒ D(f ) (x1 ,x2 ,...,xn )→(p1 ,p2 ,...,pn ) Ë ½º Ø Ö Ò ÐÐ Ö ¾¼¼ × f (x1 , x2 , . . . , xn ) = f (p1 , p2 , . . . , pn ). Ö× Ñ ÐÐØ ÐÐÙÑ ÔÙÒ ØÙÑ × Ê ÐÖ ÒÒ ÖÑ Ò × × Ñ ÐÐØ × Ò׺ ÒÚ Ð ÙÖ º Å ÐÐ Ö ËØ Ö Ö º½ Ë Ð Ö Ò Ò º (x1 , x2 , . . . , xn ) Ò Ö×Ú Ö ÝØÙÒÒ Ö ÚÖ Ð ÒÒ Ä ØÙÑ ÔÙÒ Ø ÓÔÒ × º ÀÐÙØ Ð Ö Ò Ò ÁÁ ÙÖº ÚÖ ÐÐ f (x1 , x2 , . . . , xn ) ÐÖ Ö× ÒÒ ÐÖ Ò Ö×Ú n Ö ÝØÙѺ ÝÖ Ö Ä ØÙÑ × Ñ x= Ò¹ ØÐ f Ó ÐÙ ÙØ Ò ÙÑ ÔÙÒ Ø ÒÒ xº ÀÐÙØ Ð ÖÙÑ Ö ÐÖ Ø ÐÐ Ø f xk ÔÙÒ Ø ÒÙÑ x × ÑÑ Ö fk (x) = lim ÑÖ Ú Ð Ö Ø Ðº ´À Ö ×Ø Ò ÙÖ Ö× Ñ Ö ½ºµ Ä ØÙÑ f (x + hek ) − f (x) h→0 h ÝÖ Ö Ú ÙÖ ÒÒ × Ñ ÖÑ ¼ ÐÐÙÑ Ò ØÙÑ Ò Ñ ek k ¹Ø º¾ Ë Ð Ö Ò Ò º f ÚÖ ÐÐ ØÚ ÑÙÖ Ö ÝØÙÑ x Ó yº f Ë ÐÖ ÒÙÑ f1 (x, y ) = lim Ó h→0 f (x + h, y ) − f (x, y ) h ´ ÐÙØ ÑºØºØº xµ f2 (x, y ) = lim ÑÖ Ð Ò ÖÙ Ø Ðº f (x, y + k ) − f (x, y ) k→0 k f ÚÖ ÐÐ Ö ÑÙÖ ´ ÐÙØ f Ѻغغ y µ, º¿ Ë Ð Ö Ò Ò º Ä ØÙÑ Ö ÝØÙÑ x¸ y Ó zº f f f Ë ÐÖ ÒÙÑ f1 (x, y, z ) = lim f (x + h, y, z ) − f (x, y, z ) h→0 h f (x, y + k, z ) − f (x, y, z ) k→0 k f (x, y, z + l) − f (x, y, z ) l z = f (x, y )º Ñ× ´ ÐÙØ ÑºØºØº xµ, y µ, z µ, f2 (x, y, z ) = lim Ó ´ ÐÙØ ÑºØºØº f3 (x, y, z ) = lim l→0 ÑÖ Ð Ò ÖÙ Ø Ðº ´ ÐÙØ ÑºØºØº º Ê Ø ØØÙÖº ÐÙØ ÙÖ Ê ØÙÑ Ð ÓÒ Ö Ö Ø ØØÙÖ Ø ×Ø Ú Ø Ò f¸ Ñ ÒÒ Ö× ∂z ∂ = f (x, y ) = f1 (x, y ) = D1 f (x, y ) = fx (x, y ) = Dx f (x, y ) = ∂x f (x, y ) = · · · ∂x ∂x Ó ∂z ∂ = f (x, y ) = f2 (x, y ) = D2 f (x, y ) = fy (x, y ) = Dy f (x, y ) = ∂y f (x, y ) = · · · ∂y ∂y ÖÚ Ð Ú Ð ÙÑ Ø ÙÐ Ò Ö¸ Ø Ð Ð Ñ× ÐÙØ Ù f Ú ÒÙÑ ÔÙÒ Ø (x, y ) = (a, b) ÖÙ Ñ× Ö Ñ ∂z ∂x Ó = (a,b) ∂ f (x, y ) ∂x ∂ f (x, y ) ∂y = f1 (a, b) = D1 f (a, b) (a,b) ∂z ∂y = (a,b) = f2 (a, b) = D2 f (a, b). (a,b) º Ë ØÒ Ò º (a, b, f (a, b)) Ó ×Ò ÖØ ÔÐ Ò ×Ø ÖÙÑ Ö ÐÙØ ÙÒ Ò ÝÖ Ö ÙÖÒ z = f (x, y ) Ö f1 (a, b) Ó f2 (a, b) × Ù Ö ×Ò ÖØ ÔÐ Ò Ö× ÐÖ Ò ÔÙÒ Ø ÒÙÑ Öº ÙÖ (a, b, f (a, b)) + s(1, 0, f1 (a, b)) + t(0, 1, f2 (a, b)), Ú ÙÖ ÒÒ n = f1 (a, b)i + f2 (a, b)j − k = (f1 (a, b), f2 (a, b), −1) Ö Ú ÖÚ ÙÖ ×Ò ÖØ ÔÐ Ò Ó Ò ×Ò ÖØ ÔÐ Ò× Ò× Ö z = f (a, b) + f1 (a, b)(x − a) + f2 (a, b)(y − b). º Ë Ð Ö ÒÒ º Ñ ÓÖÑ ÐÙÒÙÑ Ê ØÙÑ z = f (x, y )º ÒÒ Ö× ×Ø × ÐÙØ ÙÖ f ÖÙ × ÐÖ Ò Ö ∂ 2z ∂ ∂z = f11 (x, y ) = fxx (x, y ), = 2 ∂x ∂x ∂x ∂ 2z ∂ ∂z = f22 (x, y ) = fyy (x, y ), = 2 ∂y ∂y ∂y ∂ ∂z ∂ 2z = = f21 (x, y ) = fyx (x, y ), ∂x∂y ...
View Full Document

This note was uploaded on 01/31/2011 for the course MATH 203 taught by Professor Röggi during the Spring '10 term at Uni. Iceland.

Ask a homework question - tutors are online